Scalable localization system using ultra wide-band impulse radio - Lee, Jian Xing (2011)
Localization is becoming a major application of wireless sensor networks. Over the past few years, research in this area has seen tremendous growth and advancement, where various ranging and localization techniques are proposed. The aim of this thesis is to illustrate some of the important aspects in the design of a wireless sensor network for ranging and localization. Emphasis on the efficiency and practical aspects of different schemes are given, and novel techniques to improve on both aspects are proposed. In a practical deployment of wireless sensor nodes, there are many factors that can affect the ranging accuracy such as noise, transmitter and receiver delays, Non Line of Sight (NLOS), synchronization among the sensor nodes, power, energy consumption, cost, crystal clock time drift, the nodes having different reply time, etc. This thesis focuses on how crystal clock time drift of the wireless sensor nodes and the sensor nodes having different reply time affect the ranging performance. Discussions are made on the different ranging techniques and why the selection of the Time of Arrival technique is chosen to determine the ranges between the individual nodes. Furthermore, the use of Time of Arrival technique to overcome wireless sensor nodes crystal clock time drift and their different reply times are analyzed. As a typical wireless sensor network consists of a large number of sensor nodes, it poses a requirement for time and energy efficient ranging performance without sacrificing its accuracy. The Time of Arrival technique is modified to cater for large wireless sensor network and at the same time, to achieve good ranging accuracy by compensating the time drift. The base stations need not be synchronized in time with the modified ranging algorithm.